ИНФОРМАЦИОННАЯ БЕЗОПАСНОСТЬ ЛИЧНОСТИ В ЭПОХУ ИНТЕРНЕТ: СОЦИАЛЬНО-ПСИХОЛОГИЧЕСКИЕ АСПЕКТЫ - Бордюгова, Т. Г.; Гинзбург, М. М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Статья посвящена проблеме информационной безопасности личности в эпоху Интернет. Информация, поступающая из различных источников, в том числе всемирной паутины, оказывает непосредственное непрерывное влияние на психику человека, его систему ценностей, привычки, мотивацию и пр. Внедрение современных информационных технологий в «приватную» сферу личности актуализирует рассмотрение проблемы информационной безопасности в социально-психологическом аспекте. Т.Г. Бордюгова, М.М. Гінзбург ІНФОРМАЦІЙНА БЕЗПЕКА ОСОБИСТОСТІ В ЕПОХУ ІНТЕРНЕТ: СОЦІАЛЬНО- ПСИХОЛОГІЧНІ АСПЕКТИ Стаття присвячена проблемі інформаційної безпеки особистості у епоху Інтернет. Інформація, що поступає з різноманітних джерел, у тому числі всесвітної павутини, безпосередньо та безперервно впливає на психіку людини, її систему цінностей, звички, мотивацію тощо. Проникнення сучасних інформаційних технологій у «приватну» сферу особистості робить актуальним розгляд проблеми інформаційної безпеки у соціально- психологічному аспекті. Ключові слова: інформаційна безпека, особистість, система цінностей, інтернет. T. Bordyugova, M. Ginzburg INFORMATIONAL SECURITY OF THE PERSONALITY IN THE AGE OF THE INTERNET: SOCIAL AND PSYCHOLOGICAL ASPECTS This article is devoted to the problem of informational security of the personality in the age of Internet. Information, that comes from different sources including World Wide Web, influence directly and persistently on human psychic, his system of values, habits, motivation etc. The introduction of modern information technologies in a “private” personal sphere submits the problem of informational security in social and psychological aspects for consideration. Key words: informational security, personality, system of values, internet.